A Green's function approach to modeling molecular diffraction in the limit of ultra‐thin gratings. Issue 9 (October 2015) - Brand, Christian; Fiedler, Johannes; Juffmann, Thomas; Sclafani, Michele; Knobloch, Christian; Scheel, Stefan; Lilach, Yigal; Cheshnovsky, Ori; Arndt, Markus
Abstract : The Casimir‐Polder interactions between a complex organic molecule and material gratings arising in matter‐wave interferometry are described with a Green's function approach. The effects of the internal temperature on molecular rotation and vibration are considered. The results are compared with a simplified theoretical description and experimental data. Abstract : In recent years, matter‐wave diffraction at nanomechanical structures has been used by several research groups to explore the quantum nature of atoms and molecules, to prove the existence of weakly bound molecules or to explore atom‐surface interactions with high sensitivity. The particles' Casimir‐Polder interaction with the diffraction grating leads to significant changes in the amplitude distribution of the diffraction pattern. This becomes particularly intriguing in the thin‐grating limit, i.e. when the size of a complex molecule becomes comparable with the grating thickness and its rotation period comparable to the transit time through the mask. Here we analyze the predictive power of a Green's function scattering model and the constraints imposed by the finite control over real‐world experimental factors on the nanoscale.